Pelatihan “Pembuatan Bakso Ikan Tuna” untuk Menumbuhkan Jiwa Wirausaha pada Mahasiswa - Jakub Saddam Akbar; Kartyka Nababan; Mustapa Mustapa; Stefan Marco Rumengan; Djakariah Djakariah (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
The "Tuna Fish Ball Making" training aims to foster entrepreneurial spirit among students. Through this training, students not only gain technical knowledge in producing tuna fish balls but also acquire practical skills that can be applied to independent ventures. Tuna is chosen as the main ingredient because it is rich in nutrients and has significant market potential. This training covers the entire production process, from selecting raw materials and processing techniques to product packaging. Additionally, it includes material on marketing strategies, business management, and market analysis to strengthen students' understanding of the business world. This training is expected to enhance student's skills and knowledge in entrepreneurship and motivate them to create new business opportunities. Consequently, it is hoped that young, creative, and innovative entrepreneurs will emerge, contributing to reducing unemployment and boosting the economy. The results of this training show a significant increase in students' interest and readiness to enter the entrepreneurial world, as well as a better understanding of the importance of innovation and sustainability in business. Overall, this training has a positive impact on shaping the entrepreneurial mentality among students, making them more prepared to face future challenges.